Poster 119: Outcomes after Surgery for Thoracic Outlet Syndrome in Professional Baseball Players: A Matched Cohort Analysis. Issue 7 (30th July 2022) - Chalmers, Peter; Erickson, Brandon; Thompson, Robert; Pearl, Gregory; Romeo, Anthony; Hoenecke, Heinz; Fronek, Jan; Chauhan, Aakash
Objectives: Determine the performance and return to play (RTP) outcomes for professional baseball players that undergo surgical treatment for thoracic outlet syndrome. Methods: All professional baseball players who underwent surgical treatment of TOS between 2010-2017 were identified using the major league baseball (MLB) HITS (Health and Injury Tracking System) database. Demographic and performance data (pre and post-surgery) for each player was recorded. Standard demographic and return to play outcomes were measured for all players and compared between different types of TOS and league status. Performance variables were analyzed for pitchers and compared to a 1:1 matched set of control pitchers. Results: Overall, 52 players underwent surgery for TOS of which 46 (88%) were pitchers. Neurogenic TOS was the most common and seen in 69% of players. Venous TOS was seen in 29% of players, and a single player had arterial TOS. Following TOS surgery, 79% of players returned to play at the same level (RTSP) and played at least 3 years after surgery. There was no differences in RTSP rate based on the type of TOS. There was no statistically significant difference in RTP and RTSP rates between major and minor league players. In pitchers only, there was a 76% RTSP, which was not different from the natural attrition of control pitchers (p=0.874). Following TOS surgery, pitchers saw a decline in several performance metrics, but not statistically different when compared to the control pitchers. This indicated that the decline in performance following TOS surgery was similar to the decline seen in healthy professional pitchers as they age. Conclusions: The most common type of TOS seen in professional baseball players is neurogenic. The RTSP rate following surgery for TOS in all professional baseball players is 79%. There was no statistically significant difference in ability to RTP based on the type of TOS or league status. Pitchers who underwent surgery for TOS had no significant difference in pitching performance metrics following surgery compared to matched controls. Overall, surgery for thoracic outlet syndrome can help prolong a professional baseball players career and help pitchers maintain their performance over time similar to their peers who have not had surgery for TOS.